Factors that impact dysphagia and discontinuance of oral intake in patients with progressive supranuclear palsy - Iwashita, Yuki; Umemoto, George; Fujioka, Shinsuke; Arahata, Hajime; Dotsu, Yuriko; Oike, Asami; Tsuboi, Yoshio (Frontiers in Neurology, 2023)
To evaluate the swallowing function in the advanced stages of progressive supranuclear palsy (PSP) and clarify the factors that lead to adjustment of food consistency and discontinuation of oral intake.A total of 56 patients with PSP were recruited. Based on medical records, information about the basic attributes, clinical features (including axial rigidity and dementia), food intake, the results of a videofluoroscopic swallowing study (VFSS), and the timing of nasogastric tube transition and gastrostomy were extracted. From the VFSS images, the presence or absence of aspiration and retrocollis were assessed. The average age at the onset, diagnosis, and the final follow-up examination were 67.6±6.4 years, 71.6±5.8 years, and 75.4±5.6 years, respectively. The average duration of illness was 64.6±42.8 months. Twenty-four individuals (42.9%) were continuing oral intake, while 32 were tube-fed, among whom 16 (50.0%) underwent gastrostomy tube placement.There were significant differences in the duration from the disease onset to tube feeding between the patients with and without cognitive decline at the time of the diagnosis (p<0.01) and in the duration from the initial VFSS to tube feeding between the patients with and without aspiration on the initial VFSS (p<0.01). There were significant differences in the duration from the diagnosis to tube feeding and from the initial VFSS to tube feeding between patients with and without axial rigidity at the time of the diagnosis (p<0.05 and p<0.05, respectively). Additionally, there was a significant association between axial rigidity and retrocollis (p<0.01). Cognitive decline, axial rigidity and retrocollis, which are associated with the deterioration of dysphagia in PSP, are the highest risk factors for the discontinuation of oral intake. The early identification of these factors associated with the progression of dysphagia can contribute to the improvement of patient care and management.